Revisiting brain gene expression changes and protein modifications tracking homeostatic sleep pressure - Valérie Mongrain; Marcos G. Frank; Tanya Leduc (npj Biological Timing and Sleep)
Abstract This review describes how transcriptomic/proteomic studies have contributed identifying molecular markers of sleep homeostasis and offers a perspective on the need to interrogate more comprehensively different dynamics, brain regions, and cell types. Modifications in molecular dynamics with development/aging are also emphasized. We suggest the concept of sleep homeostasis to be regarded as a variety of homeostats (not a single one) serving different functions for the brain across the lifespan.